BIM Handbook: A guide to Building Information Modeling for owners, managers, designers, engineers and contractors (Construction Economics and Building, 2012)
2nd EditionC Eastman, P Teicholtz, R Sacks and K Liston ISBN: 978-0-470-54137-1 (Hardcover) 648 pages, 2011, AUD $105.00; NZD $120.00, USD 85.00, GBP57.50, EUR 68.00E-book version ISBN: 978-1-1180-2169-9 544 pages 2011 AUD $84.99 / NZD $99.99, USD69.99, GBP 47.99, EUR 54.99